Light-induced shifts in opsin gene expression in the four-eyed fish Anableps anableps - Salgado, Daniele; Mariluz, Bertha R.; Araujo, Maysa; Lorena, Jamily; Perez, Louise N.; Ribeiro, Rafaela de L.; Sousa, Josane de F.; Schneider, Patricia N. (Frontiers in Neuroscience, 2022)
The development of the vertebrate eye is a complex process orchestrated by several conserved transcriptional and signaling regulators. Aside from partial or complete loss, examples of exceptional modifications to this intricate organ are scarce. The unique eye of the four-eyed fish Anableps anableps is composed of duplicated corneas and pupils, as well as specialized retina regions associated with simultaneous aerial and aquatic vision. In a previous transcriptomic study of the A. anableps developing eye we identified expression of twenty non-visual and eleven visual opsin genes. Here, we surveyed the expression territories of three non-visual melanopsins genes (opn4x1, opn4x2, opn4m3), one teleost multiple tissue opsin (tmt1b) and two visual opsins (lws and rh2-1) in dorsal and ventral retinas. Our data showed that asymmetry of non-visual opsin expression is only established after birth. During embryonic development, while inside pregnant females, the expression of opn4x1, opn4x2 and tmt1b spans the whole retina. In juvenile fish (post birth), the expression of opn4x1, opn4x2, opn4m3 and tmt1b genes becomes restricted to the ventral retina, which receives aerial light. Raising juvenile fish in clear water instead of the murky waters found in its natural habitat is sufficient to change gene expression territories of opn4x1, opn4x2, opn4m3, tmt1b and rh2-1, demonstrating that different lighting conditions can shift opsin expression and potentially contribute to changes in spectral sensitivity in the four eyed fish.